KETIDAKPASTIAN LINGKUNGAN ORGANISASI BERIMPLIKASI TERHADAP PEMILIHAN SISTEM PENGENDALIAN MANAJEMEN - Muhammad Nur El Farabi (JABE (Journal of Applied Business and Economic), 2020)
Management control systems in organizations are one of the important topics in management accounting. The selection of the right management control system is actually influenced by environmental uncertainty in the organization. It is necessary to review the literature regarding the implications of the uncertainty of the organization's environment on the selection of a management control system. This article is compiled based on the ideas supported by a literature review using content analysis. The content analysis stage starts from searching for relevant articles, selecting articles and collecting criteria for each article. The result is that the system changes that will be used are closely related to the organizational structure, objectives, and implementation of planning. This is because the control system itself actually means as a device of interconnected communication structures that facilitate information processing with the aim of helping management coordinate the parts that exist to achieve organizational goals on an ongoing basis. The uncertainty of the organization's environment clearly has on the selection of a management control system, so that with a rapidly changing environment the organization has implications for the need for more detailed information in order to maximize the function of the management control system.